Randomized open-label trial of dextromethorphan in Rett syndrome. (17th October 2017) - Smith-Hicks, Constance L.; Gupta, Siddharth; Ewen, Joshua B.; Hong, Manisha; Kratz, Lisa; Kelley, Richard; Tierney, Elaine; Vaurio, Rebecca; Bibat, Genila; Sanyal, Abanti; Yenokyan, Gayane; Brereton, Nga; et al.
Abstract : Objective: To determine safety and perform a preliminary assessment of dose-dependent efficacy of dextromethorphan in normalizing electrographic spikes, clinical seizures, and behavioral and cognitive functions in girls with Rett syndrome. Methods: We used a prospective randomized, open-label trial in fast metabolizers of dextromethorphan to examine the effect of dextromethorphan on core clinical features of Rett syndrome. Interictal spike activity and clinical seizures were determined using EEG and parent reporting. Cognitive data were obtained using the Mullen Scales of Early Learning and Vineland Adaptive Behavior Scales, while behavioral data were obtained from parent-completed checklists, the Aberrant Behavior Checklist–Community Version, and the Screen for Social Interaction. Anthropometric data were obtained according to the National Health and Nutrition Examination Survey. The Rett Syndrome Severity Scale provided a clinical global impression of the effect of dextromethorphan on clinical severity. Results: Dextromethorphan is safe for use in 3- to 15-year-old girls with Rett syndrome. Thirty-five girls were treated with 1 of 3 doses of dextromethorphan over a period of 6 months. Statistically significant dose-dependent improvements were seen in clinical seizures, receptive language, and behavioral hyperactivity. There was no significant improvement in global clinical severity as measured by the Rett Syndrome Severity Scale. Conclusions: Dextromethorphan is a potent noncompetitive antagonist of the NMDA receptor channel that is safe for use in young girls with Rett syndrome. Preliminary evidence suggests that dextromethorphan may improve some core features of Rett syndrome. Classification of evidence: This study provides Class IV evidence that dextromethorphan at various doses does not change EEG spike counts over 6 months, though precision was limited to exclude an important effect.